Strategies to optimize modelling habitat suitability of Bertholletia excelsa in the Pan-Amazonia - Tourne, D.C.M.; Ballester, M.V.R.; James, P.M.A.; Martorano, L.G.; Guedes, M.C.; Thomas, E. (Wiley, 2019)
Amazon‐nut (Bertholletia excelsa) is a hyperdominant and protected tree species, playing a keystone role in nutrient cycling and ecosystem service provision in Amazonia. Our main goal was to develop a robust habitat suitability model of Amazon‐nut and to identify the most important predictor variables to support conservation and tree planting decisions.